Carbon Nanomaterials: A New Sustainable Solution to Reduce the Emerging Environmental Pollution of Turbomachinery Noise and Vibration - Jia, Xiao Qi; Li, Song Yu; Miu, Hong Jiang; Yang, Tuo; Rao, Kun; Wu, Dong Yang; Cui, Bao Ling; Ou, Jun Lang; Zhu, Zu Chao (Frontiers in Chemistry, 2020)
The vibration and noise resulted from turbomachinery, such as fans, compressors, and centrifugal pumps, are known to bring considerable disturbance and pollution to the machine itself, the environment, and the operators. Hence, how to cope with the vibration and noise has become a recent research focus. With the advancement of materials science, more and more new nanomaterials have been applied in the field of noise and vibration reduction. To be specific, carbon-based nanomaterials, such as carbon fibers, carbon nanotubes, and graphenes, have achieved outstanding results. Carbon nanocomposites, such as carbon nanofibers, carbon nanotubes, and graphenes, are characterized by their low densities, high strengths, and high elastic moduli, all of which made carbon nanocomposites the most promising vibration and noise reduction composites, thanks to their damping properties, compatibilities, noise and vibration absorption qualities, as well as wide wave-absorbing frequency bands. In light of this, this paper summarizes the progresses and application prospects of such carbon nanocomposites as carbon nanofibers, carbon nanotubes, and graphenes in the field of turbomachinery vibration and noise reduction.